Pemberdayaan Pedagang Baduy Untuk Membuat “Jazanduy” (Jajanan Bergizi Anak Baduy) Sebagai Upaya Penurunan Angka Stunting Di Baduy, Lebak, Banten - Wahab, Revalita; Ningrum, Nathalia; Soegiarto Marpaung, Charles; Malik Hidayat, Maulana; Dafina, Maya; Philip (JURNAL ABDIMAS KESEHATAN TERPADU, 2025)
Stunting in Indonesia remains a chronic nutritional problem among children that requires immediate attention. Various efforts have been made to address this issue. The prevalence of stunting among children in the Baduy area remains high, one of the contributing factors being inadequate nutritional intake, particularly from snacks sold in the community. Baduy street vendors play a crucial role in selling these snacks. This community service program (PKM), conducted from September to November 2025, targeted the local vendors as participants. The educational intervention on JAZANDUY (Nutritious Snacks for Baduy Children) produced positive and statistically significant results (p<0.005). The program also generated several outputs, including a recipe booklet, video documentation, scientific publication, and eco-friendly packaging design. This initiative effectively improved the knowledge and skills of Baduy vendors in providing healthy snacks, potentially contributing to reducing stunting rates and strengthening the local economy.